1995
DOI: 10.1056/nejm199507273330404
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Tuberculosis among Regular Patrons of a Neighborhood Bar

Abstract: The spread of tuberculosis in a neighborhood bar can be a major public health problem. The high rate of infection and disease among the contacts was unexpected and was not due to coinfection with the human immunodeficiency virus. Possible explanations include heavy alcohol use among the contacts, high infectivity of the index case, or both. Sputum cultures must be performed in tuberculin-positive contacts who have symptoms, even if the chest films are normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
9

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(107 citation statements)
references
References 24 publications
3
92
0
9
Order By: Relevance
“…Los resultados preliminares comienzan a mostrar que esta estrategia está mejorando las tasas de curación. 17 En otros países se han puesto en práctica estrategias creativas como son la administración del tratamiento en la comunidad, [18][19][20] en sitios tales como hogares, centros de trabajo y lugares de recreación como los bares, 21 con el apoyo de personas de la comunidad. 22 Es necesario que las modificaciones al programa estén orientadas al paciente y no a los sistemas de salud.…”
Section: Artículo Original Eficacia Y Eficiencia Del Tratamiento Antiunclassified
“…Los resultados preliminares comienzan a mostrar que esta estrategia está mejorando las tasas de curación. 17 En otros países se han puesto en práctica estrategias creativas como son la administración del tratamiento en la comunidad, [18][19][20] en sitios tales como hogares, centros de trabajo y lugares de recreación como los bares, 21 con el apoyo de personas de la comunidad. 22 Es necesario que las modificaciones al programa estén orientadas al paciente y no a los sistemas de salud.…”
Section: Artículo Original Eficacia Y Eficiencia Del Tratamiento Antiunclassified
“…Pioneer work on the use of fingerprinting for tracing outbreaks detected an epidemic among homeless people in Amsterdam, identified two persons contaminated during bronchoscopy on the same day in the same clinic, demonstrated that a woman contaminated her husband and showed transmission within certain families in Czechoslovakia , identified sources of infection in a pub and a discotheque (Van Embden et al 1993b) and demonstrated infection by a neighbor (GodfreyFaussett et al 1992a). The importance of transmission of TB within shelters for the homeless was also demonstrated in a study with TB patients from Australia and by means of contact investigation by IS6110-RFLP, it was shown that TB was actively transmitted in a neighborhood bar in Minneapolis, where an index case infected 41 of his contacts (Kline et al 1995). These studies clearly demonstrate the value of RFLP analysis in situations where traditional contact tracing alone would not be able to detect clusters of TB; it also shows that single, highly infectious cases can have a severe influence on TB transmission within a community and, as a consequence, on TB programs.…”
Section: Applications Of Molecular Strain Typing As An Additional Toomentioning
confidence: 99%
“…It is estimated that 1 billion persons worldwide are infected with Mycobacterium tuberculosis [2]. Tuberculosis has thus not been eradicated [4] and recently an outbreak was reported [8]. Extrapulmonary involvement is present in 18% of the cases reported in the United States [2] and pleurisy is frequently caused by reactivation of the disease [11.…”
Section: Introductionmentioning
confidence: 99%